Social conflict management in Elementary Schools and its implications for character building: A case study of SDN 2 Kalipuro - Yasin, Nur Ali (Priviet Social Sciences Journal, 2025)
Conflict between students is an inseparable part of the dynamics of social interactions in elementary school environments. If properly managed, conflict can be an effective means of character education. This study aims to describe the forms and causes of conflict that occurred at SDN 2 Kalipuro, identify conflict management strategies implemented by the school, and analyze their implications for strengthening students’ character. This study used a qualitative approach with a case study type. Data collection techniques included observations, interviews, and documentation. The results of the study indicate that student conflicts in elementary schools are generally mild and caused by differences in interests, momentary emotions, and lack of social communication skills. Schools implement various conflict management strategies such as collaborative approaches, mediation, counseling, and strengthening value-based regulations. These strategies have a positive impact on the formation of student characters, especially in terms of tolerance, responsibility, empathy, honesty, and self-control. Thus, conflict management carried out in an educational and sustainable manner can be an integral part of character education in elementary schools.